2017
DOI: 10.1128/jcm.02275-16
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Carbapenem Inactivation Method (CIM) for Detection of IMP Metallo-β-Lactamase-Producing Enterobacteriaceae

Abstract: Carbapenem-resistant Enterobacteriaceae (CRE) strains have become globally distributed in the past decade, resulting in concern over the control of hospital infections and antimicrobial therapies (1, 2). The majority of CRE isolates are carbapenemase-producing Enterobacteriaceae (CPE) strains, so early detection of CPE strains is essential for providing optimal antimicrobial therapies and preventing horizontal transmission. In 2015, van der Zwaluw et al. reported the carbapenem inactivation method (CIM), a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Using PCR, 40 (74%) of these isolates were found to contain a carbapenemaseencoding gene. These results of CIM are consistent with other findings stated by some other researches [14,[15][16][17][18][19]. With respect to our research, CIM for the first time in Iran was found to be very efficient and low-cost in the recognition of carbapenemaseproducing K. pneumoniae isolates.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Using PCR, 40 (74%) of these isolates were found to contain a carbapenemaseencoding gene. These results of CIM are consistent with other findings stated by some other researches [14,[15][16][17][18][19]. With respect to our research, CIM for the first time in Iran was found to be very efficient and low-cost in the recognition of carbapenemaseproducing K. pneumoniae isolates.…”
Section: Resultssupporting
confidence: 92%
“…MIC results for five antibiotics Cp, IMP, MP, CAZ, and CRO showed a high level of resistance (MIC≥4). The phenotypic confirmatory test showed that among the 54 isolates, 54 (100%) were ESBL producers (14). The PCR test of the ESBLproducing isolates showed that TEM 24 (44.4%) isolates were positive for the blaTEM gene, 40 (80.1%) positive for the blaCTX-M groups, and 30 (55.6%) isolates had the blaSHV gene.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several publications on the CIM assay have been published, reinforcing the usefulness and improvements of this phenotypic method [40][41][42]. In order to improve the…”
Section: Discussionmentioning
confidence: 94%